The skinny gut diet : balance your digestive system for permanent weight loss - Watson, Brenda; Jones, Jamey; Smith, Leonard, 1942- (Harmony Books, 2014)
"A breakthrough diet book from gut expert Brenda Watson, this will be the first weight loss program using the latest scientific information on digestive health and sustainable fitness. An easy, nutritious, and delicious diet"--